The determinants of saving behaviors among UMK students - Mohamad Fakhrulhakim Mohd Daud; Hemalatha Muniandy; Nursriana Basri; Nursyamimi Sulaiman (2023)
Saving which is the most typical strategy for people to manage their wealth, is the last manifestation of surplus in an economic cycle. due to the importance of saving practises in guaranteeing the long-term financial security of university students. There aren't many studies being conducted right now that concentrate on the variables that influence college students' saving behaviors. The purpose of this study is to investigate the factors that influence students at UMK's saving behaviors. By giving users questionnaires, this study employs a quantitative design. A total of 150 respondents who attend UMK participated in the basic random sampling technique used for data collection. The descriptive, reliability, spearman's correlation, and chi squared tests are employed in this study to examine the data using the Statistical Package for Social Science (SPSS) programme. These tests were used to determine whether the three variables had any bearing on how Malaysian university students in Kelantan saved money. The findings indicate that every element has a favourable link with saving behaviors. The overall results of the study show a positive association between financial literacy, parental socialization, and self control, with self control having the biggest influence of the three independent factors on saving behaviors. In addition to significantly eliminating the educational gap, this research has practical importance for university students, parents, commercial banks serving universities, and other relevant parties. In reality, this research can assist retail banks in creating efficient strategies for connecting with young savers, especially college students. Additionally, it provides policymakers with information on how to encourage students to save by raising their level of financial literacy..Last but not least, it gives parents insight into how to ensure that their children develop healthy saving habits.